Therapeutic potential of Bifidobacterium longum subsp. infantis B8762 on gut and respiratory health in infant - Richmond, Rocky Vester; Mageswary, Uma; Ali, Adli; Taib, Fahisham; Koo, Thai Hau; Yusof, Azianey; Abd Hamid, Intan Juliana; Zhao, Feiyan; Nik Abd Rahman, Nik Norashikin; Hasan, Taufiq Hidayat; Zhang, Heping; Liong, Min-Tze (MDPI, 2025)
Respiratory tract and gastrointestinal infections in pediatric populations are major public health concerns. Addressing these challenges necessitates effective preventative and therapeutic strategies. This study assessed the efficacy of the probiotic Bifidobacterium longum subsp. infantis B8762 (0.5 × 10 power of 10 CFU) in reducing the duration and frequency of these infections in young children. In a randomized trial, 115 eligible children were assigned to either the probiotic (n = 57; 3.51 ± 0.48 months old) or placebo (n = 58; 2.78 ± 0.51 months old) group, with daily consumption for 4 weeks. The probiotic group demonstrated a lower duration of infections than the placebo group (p < 0.05). The probiotic group also showed fewer clinical visits due to respiratory and gastrointestinal problems as compared to the placebo group (p = 0.009 & p = 0.004, respectively). Oral swab samples revealed that the placebo group had higher levels of pro-inflammatory cytokine TNF-α after 4 weeks (p = 0.033), while the probiotic group demonstrated a balanced cytokine response, indicating modulation of the immune system. Genomic analysis showed that B8762 harbors various genes for the synthesis of proteins and vitamins crucial for the gut health of children. Both the clinical and genomic findings suggested that B8762 offered a therapeutic effect on gut and respiratory health in children, highlighting its potential in managing common pediatric infections.